2014
DOI: 10.1016/j.celrep.2014.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Vesicle Priming by CAPS Is Independent of Its SNARE-Binding MUN Domain

Abstract: Priming of secretory vesicles is a prerequisite for their Ca(2+)-dependent fusion with the plasma membrane. The key vesicle priming proteins, Munc13s and CAPSs, are thought to mediate vesicle priming by regulating the conformation of the t-SNARE syntaxin, thereby facilitating SNARE complex assembly. Munc13s execute their priming function through their MUN domain. Given that the MUN domain of Ca(2+)-dependent activator protein for secretion (CAPS) also binds syntaxin, it was assumed that CAPSs prime vesicles th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 43 publications
(68 reference statements)
4
23
1
Order By: Relevance
“…A recent paper indeed showed that CAPS-2 and Munc13 use different mechanisms to prime vesicles, whereas Munc13-dependent priming requires its MUN domain this domain in CAPS-2 is dispensable for priming. Instead CAPS-2 appears to require its PIP2 binding pleckstrin homology domain (Nguyen Truong et al, 2014). We found that both proteins play important stimulatory roles in DCV release from mammalian neurons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent paper indeed showed that CAPS-2 and Munc13 use different mechanisms to prime vesicles, whereas Munc13-dependent priming requires its MUN domain this domain in CAPS-2 is dispensable for priming. Instead CAPS-2 appears to require its PIP2 binding pleckstrin homology domain (Nguyen Truong et al, 2014). We found that both proteins play important stimulatory roles in DCV release from mammalian neurons.…”
Section: Discussionmentioning
confidence: 99%
“…CAPS-1 binds to PI 4,5-P2 (PIP2) (Loyet et al, 1998) and localizes to PIP2 clusters in the plasma membrane via its PIP2-binding pleckstrin homology (PH) domain (James et al, 2008). The PH domain is also required to prime secretory vesicles (Kabachinski et al, 2014; Nguyen Truong et al, 2014). Robust Ca2+ influx in our experiments likely activates phospholipase C, which hydrolysis PIP2 and may trigger CAPS-1 dispersion from synapses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the C-terminal region that encompasses MDH1 (Munc13-homology domain) and DCVBD has been reported to bind to SNARE proteins and to promote SNARE-mediated vesicle fusion (Hammarlund et al, 2008; James et al, 2009; Parsaud et al, 2013). In contrast, a recent study demonstrated that the pleckstrin homology (PH) domain located in the middle of CAPS1, but not the C-terminal region, is essential for the priming of secretory vesicles by CAPS1 (Nguyen Truong et al, 2014). However, the present study demonstrated that a single point mutation in the DCVBD, leading to the exclusive expression of edited CAPS1, induced leanness and hyperactivity in mice.…”
Section: Discussionmentioning
confidence: 96%
“…The protein is a dimer of 145 kDa subunits, exhibits Ca 2+ -dependent interaction with hydrophobic matrix, and binds to phospholipid vesicles, suggesting a membrane-associated function. CAPS1 exists in a variety of species; in vertebrates, CAPS1 has a closely related isoform called CAPS2 [5,6,7]. The CAPS family regulates secretory granule exocytosis, including monoamines and neuropeptides, as well as Golgi trafficking.…”
Section: Introductionmentioning
confidence: 99%